The influence of work discipline and workload on employee performance Andi Djemma RPH, North Luwu Regency - Zaskia, Deby; Sukri, Sukri; Basir, Adil (Goodwood Publishing, 2025)
Purpose: This study aimed to determine whether work discipline and workload affect employee performance at the Andi Djemma Regional Public Hospital (RSUD) in North Luwu Regency. Research/methodology: This study used a quantitative method. The study was conducted at the Andi Djemma RPH, North Luwu Regency, from October to November 2023. Data were collected by distributing questionnaires to 100 participants. The collected data were tested using multiple linear regression analysis with SPSS statistical software version 23 to examine the influence of the two independent variables on the dependent variable. Results: The results of the t-test show that the work discipline variable has a partial effect on employee performance at Andi Djemma RPH, North Luwu Regency, and the workload variable also has a partial effect on employee performance. The F-test results indicate that the calculated F-value is 38.376 > F-table, with a significance value of < 0.001 < 0.05, which means the result is statistically significant. This proves that work discipline and workload positively and significantly affect employee performance. Conclusions: The results suggest that strengthening tax knowledge and optimizing the accessibility and usability of digital platforms can enhance tax compliance among MSMEs. While perceived risk does not directly affect compliance, it may still play an indirect role through its interaction with other behavioral factors. Limitations: This study is limited to MSMEs in Palembang and uses self-reported data, which may introduce bias. Future research could expand to broader regions and include longitudinal data to better capture behavioral changes over time. Contribution: This study contributes to the literature by integrating behavioral and technological factors in understanding MSME tax compliance. It also offers practical insights for tax authorities to design targeted education and digitalization strategies to increase voluntary compliance.